Algorithms and Complexity 7th International Conference, CIAC 2010, Rome, Italy, May 26-28, 2010. Proceedings - Calamoneri, Tiziana; Diaz, Josep; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 7th International Conference on Algorithms and Computation, CIAC 2010, held in Rome, Italy, in May 2010. The 30 revised full papers presented together with 3 invited papers were carefully reviewed and selected from 114 submissions. Among the topics addressed are graph algorithms I, computational complexity, graph coloring, tree algorithms and tree decompositions, computational geometry, game theory, graph algorithms II, and string algorithms.
Invited Talks -- Towards a Distributed Search Engine -- Mechanisms for the Marriage and the Assignment Game -- Resilient Algorithms and Data Structures -- Session 1. Graph Algorithms I -- An Exact Algorithm for Connected Red-Blue Dominating Set -- Maximizing PageRank with New Backlinks -- Enumerating Rooted Graphs with Reflectional Block Structures -- Improved Approximations for TSP with Simple Precedence Constraints -- Polynomial Space Algorithms for Counting Dominating Sets and the Domatic Number -- Session 2. Computational Complexity -- Parameterized Complexity of Even/Odd Subgraph Problems -- Popular Matchings in the Marriage and Roommates Problems -- Bounding the Number of Tolerable Faults in Majority-Based Systems -- A Parameterized Algorithm for Chordal Sandwich -- Testing Computability by Width-2 OBDDs Where the Variable Order is Unknown -- Session 3. Graph Coloring -- Graph Unique-Maximum and Conflict-Free Colorings -- Strategic Coloring of a Graph -- Session 4. Tree Algorithms and Tree Decompositions -- Multicut Algorithms via Tree Decompositions -- The Steiner Tree Reoptimization Problem with Sharpened Triangle Inequality -- Kernelization for Maximum Leaf Spanning Tree with Positive Vertex Weights -- A Planar Linear Arboricity Conjecture -- Session 5. Computational Geometry -- On the Number of Higher Order Delaunay Triangulations -- How Simple Robots Benefit from Looking Back -- Session 6. Game Theory -- On Strategy Improvement Algorithms for Simple Stochastic Games -- Online Cooperative Cost Sharing -- Session 7. Graph Algorithms II -- On the Power of Nodes of Degree Four in the Local Max-Cut Problem -- Packing Bipartite Graphs with Covers of Complete Bipartite Graphs -- Irredundant Set Faster Than O(2 n ) -- The Complexity of Computing Minimal Unidirectional Covering Sets -- A Parameterized Route to Exact Puzzles: Breaking the 2 n -Barrier for Irredundance -- Session 8. String Algorithms -- Finding the Maximum Suffix with Fewer Comparisons -- An Algorithmic Framework for Motif Discovery Problems in Weighted Sequences -- Session 9. Network Algorithms -- Capacitated Confluent Flows: Complexity and Algorithms -- Preprocessing Speed-Up Techniques Is Hard -- Communication Requirements for Stable Marriages.
Keywords: Computer science; Computer Communication Networks; Data structures (Computer science).; Computer software; Electronic data processing; Computational complexity; Computer graphics; Computer Science; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Data Structures; Numeric Computing; Computer Graphics; Computer Communication Networks